A voice for nonprofits - Berry, Jeffrey M., 1948- (Brookings Institution Press, 2003)
"Nonprofit organizations are playing an increasingly important role in delivering basic government services. Yet they are discouraged by federal law from participating in legislative lobbying efforts - even on issues that affect their clients directly. Without the involvement of nonprofits in the governmental process, the vulnerable populations they serve are left without effective representation in the political system. A Voice for Nonprofits analyzes the effect of government restrictions on the participation of nonprofits in the policymaking process and suggests ways to address the problems."--Jacket